Taxonomy of the Dictyota ciliolata–crenulata complex (Dictyotales, Phaeophyceae) - Tronholm, Ana (2013)
We reassessed the taxonomy of dentate Dictyota species formerly attributed to D. ciliolata and D. crenulata. Both taxa have long been assumed to be broadly distributed in tropical to warm-temperate seas. Recent molecular data, however, provided evidence that D. crenulata constituted a complex of at least four species with restricted geographical distributions. Based on those results and careful morphological examination, we split D. crenulata sensu lato into D. crenulata sensu stricto restricted to Pacific Central America, D. jamaicensis with a tropical amphi-Atlantic distribution and D. canariensis and D. pleiacantha sp. nov. from Macaronesia. Morphological analysis showed that these species were distinguished by subtle morphological differences. In contrast to D. crenulata sensu lato, the wide tropical distribution of D. ciliolata was confirmed by DNA data. In addition, psbA sequence analysis did not provide evidence to segregate D. menstrualis and D. plectens from D. ciliolata.